Understanding the drivers of suicide: its influences and its functions - Kuzmina, Natalia (Kansas State University, 2022)
Suicide continues to be one of the biggest concerns in modern society globally. The understanding of suicide and suicidal ideation has evolved over time and yet there is still a lot of unknowns in how to assess, predict, and prevent suicide from happening. Continued research on suicidal ideation and behavior is essential to increase our understanding of its drivers and identify new prevention strategies. This qualitative study analyzed data on indirect and direct suicidal drivers from 35 adult participants who self-report as having suicidal ideation. Thematic analysis uncovered seven distinct themes that reflect the types of suicidal drivers experienced by participants with active and passive suicidal ideation: being a liability, feeling alienated, perceived defectiveness, low self-worth, emotional anguish, health issues, and external stressors. Some of these suicidal drivers were self-imposed while others were other-imposed. The study explored the function of suicide for participants and identified them as to provide relief, as a form of self-punishment, and to gain control. Implications for practice, policy, and research are discussed.
Keywords: Suicidal drivers; Suicidal ideation; Thwarted belongingness; Perceived burdensomeness